From awareness to action: Health Belief Model-based educational intervention to improve breast self-examination practice among college teachers in Pakistan (CRCT) - Mahar, Benazir; Osman, Malina; Ahmad Fauzi, Fatimah (Public Library of Science, 2026)
Background Breast cancer (BC) is the most common malignancy among women globally, with Pakistan showing similar trends. Teachers, especially female college teachers, are influential in health promotion. This study assessed the effectiveness of a Health Belief Model (HBM)-based educational intervention in improving breast self-examination (BSE) knowledge, beliefs, and practices. Methodology A parallel cluster-randomized controlled trial was conducted among 114 female teachers from four colleges in Hyderabad, Pakistan, with colleges as the unit of randomization. The intervention group received multimedia presentations, survivor testimonials, pamphlets, breast models, gamified quizzes, and reminders, while the control group was offered the session after study completion. Data was collected at baseline, 1-month, and 3-month follow-ups using validated Urdu questionnaires. Analyses included descriptive statistics, bivariate tests, and Generalized Estimating Equations (GEE), using the Statistical Package for the Social Sciences (SPSS) version 29. A p-value < 0.05 was considered statistically significant. Results Baseline characteristics were comparable across groups. Following the intervention, BSE practice improved significantly in the intervention group. At 1 month, participants were 5.7 times more likely to practice BSE (Adjusted Odds Ratio (AOR) = 5.724, p < 0.001), rising to 26.5 times at 3 months (AOR = 26.500, p < 0.001). Knowledge scores also increased significantly (p < 0.001). Significant between-group differences were observed in perceived susceptibility, severity, benefits, barriers, self-efficacy, and cues to action (all p≤0.001). Conclusion HBM-based intervention effectively enhanced BSE knowledge, beliefs, and practices while reducing barriers. Findings emphasize the value of structured educational interventions in promoting preventive health behaviors among female educators.